A phase 2 clinical trial of combined BRAF/MEK inhibition for BRAFV600E-mutated multiple myeloma - Giesen, Nicola; Chatterjee, Manik; Scheid, Christof; Poos, Alexandra; Besemer, Britta; Miah, Kaya; Benner, Axel; Becker, Nicole; Moehler, Thomas; Metzler, Ivana; Khandanpour, Cyrus; Seidel-Glätzer, Andrea; et al. (Blood, 2023)
Activating BRAF mutations are found in a small subset of patients with newly diagnosed multiple myeloma, but prevalence increases in late-stage, refractory disease, and the mutations are associated with adverse outcome. This prospective single-arm, open-label, multicenter phase 2 trial assessed the efficacy and safety of combined BRAF/MEK inhibition, using encorafenib and binimetinib, in patients with relapsed/refractory multiple myeloma (RRMM) carrying a BRAFV600E mutation. Patients received 450 mg encorafenib once daily and binimetinib 45 mg twice daily. The primary end point was the overall response rate achieved within the first year after start of treatment according to International Myeloma Working Group criteria. Twelve RRMM patients with a median of 5 prior lines of therapy were enrolled. The overall response rate was 83.3%, with 10 patients achieving at least a partial response. The median progression-free survival was 5.6 months, and overall survival was 55% at 24 months. Emerging resistance to therapy was driven by RAS mutations and structural variants involving the BRAF locus. This is the first prospective clinical trial to demonstrate that combined BRAF/MEK inhibition is highly effective in patients with BRAFV600E-mutated RRMM, and it represents a successful targeted precision medicine approach in this disease. This trial was registered at www.clinicaltrials.gov as #NCT02834364.
Gesehen am 15.06.2023